2022
DOI: 10.1002/jcla.24520
|View full text |Cite
|
Sign up to set email alerts
|

miR‐548d‐3p inhibits the invasion and migration of gastric cancer cells by targeting GKN1

Abstract: Background:The aim of this study was to explore the function and mechanism of GKN1 in gastric cancer (GC) progression.Methods: Firstly, we used GEO2R to perform differential gene analysis on GSE26942 and GSE79973 and constructed the protein-protein interaction network of differential genes by STRING. Next, the cytoHubba, Mcode plugins, and GEPIA were used to obtain our follow-up research object GKN1. Then, the function of GKN1 in GC was verified by scratch and transwell assay in GC cells. We further analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In a recent meta-analysis, Xu et al [142] found that miR-21, miR-106, miR-421, and miR-223 have better diagnostic efficacy for GC, with miR-421 particularly useful as an auxiliary diagnostic indicator for GC; the AUC of its diagnostic GC can reach 0.92. More studies found that miR-548d-3p [153], miR-4742-5p [154], and miR-23b [145], which are significantly up-regulated in GC, and miR-137-3p [152], miR-148a [144], and miR-875-5p [143], which are significantly down-regulated in GC, are effective in distinguishing GC patients from healthy control individuals. In terms of metastasis, miR-17-5p and miR-4742-5p are up-regulated in GC.…”
Section: Clinical Application Of Ncrnas In Gc Liquid Biopsymentioning
confidence: 99%
“…In a recent meta-analysis, Xu et al [142] found that miR-21, miR-106, miR-421, and miR-223 have better diagnostic efficacy for GC, with miR-421 particularly useful as an auxiliary diagnostic indicator for GC; the AUC of its diagnostic GC can reach 0.92. More studies found that miR-548d-3p [153], miR-4742-5p [154], and miR-23b [145], which are significantly up-regulated in GC, and miR-137-3p [152], miR-148a [144], and miR-875-5p [143], which are significantly down-regulated in GC, are effective in distinguishing GC patients from healthy control individuals. In terms of metastasis, miR-17-5p and miR-4742-5p are up-regulated in GC.…”
Section: Clinical Application Of Ncrnas In Gc Liquid Biopsymentioning
confidence: 99%